Eficácia e ecotoxicidade do diquat em mistura com fontes de cobre para controle de Ceratophyllum demersum e alga unicelular e filamentosa - Garlich, Nathalia [UNESP] (2015)
The excessive growth of weeds and algae in aquatic environments, arising from urban and industrial activities, hinder the multiple uses of water. The application of an herbicide associated with an algaecide product may be more effective in controlling weeds and algae. The objective of this research were to evaluate the effectiveness of diquat, copper oxychloride, copper hydroxide and the associations diquat + 0.1% copper oxychloride and diquat + 0.1% copper hydroxide in control of the submerged aquatic macrophyte Ceratophyllum demersum, unicellular algae Ankistrodesmus gracilis and the filamentous algae Pithophora kewesis and to estimate the acute toxicity (LC50/EC50) for non-target organisms Hyphessobrycon eques, Pomacea canaliculata, Lemna minor and Azolla caroliniana. For C. demersum control the associations diquat + 0.1% copper oxychloride and Diquat + 0.1% copper hydroxide were more effective.For A. gracilis control the copper oxychloride and copper hydroxide were more effective if applicated individually and none of the tested chemicals were effective on P. kewesis control. The macrophyte L. minor was the most sensitive bioindicator to the tested chemicals and the fish H. eques was the least sensitive